Post‐procedure protocol to facilitate next‐day discharge: Results of the multidisciplinary, multimodality but minimalist TAVR study. Issue 2 (29th November 2019) - Lauck, Sandra B.; Sathananthan, Janarthanan; Park, Julie; Achtem, Leslie; Smith, Amanda; Keegan, Patricia; Hawkey, Marian; Brandwein, Russell; Webb, John G.; Wood, David A.; ,
Abstract: Background: Evidence is lacking to standardize post‐procedure care after transcatheter aortic valve replacement (TAVR). Objective: We report on the findings of the post‐procedure sub‐study of the multimodality, multidisciplinary but minimalist TAVR (3M TAVR) study. Methods: A standardized protocol to guide monitoring, early mobilization, reconditioning, communication, and criteria‐driven discharge was implemented in a multicenter, prospective, sequential case series study in 13 North American low, medium, and high‐volume centers in 2015–2017. Outcome measures pertaining to post‐procedure care included avoidance of invasive lines and delirium, in‐hospital bed utilization, patient disposition at the time of discharge, and 30‐day use of nonelective medical services. Results: Four hundred eleven participants were enrolled. In the post‐procedure phase, 365 (88.8%) participants were admitted without a temporary pacemaker; urinary catheterization was avoided in 402 (97.8%) participants. Of note, 91.7% received care in a single unit (critical care: 72.5%; cardiac telemetry: 19.2%); 99.0% were discharged home. At the time of 30‐day follow‐up, 6 (1.6%) participants required admission to a rehabilitation or a skilled nursing facility; 30‐day emergency department visits were 13.5%. Conclusions: The implementation of the 3M TAVR standardized accelerated reconditioning protocol is a safe and effective strategy to facilitate next‐day discharge home after TAVR in centers of varying size.